Qtls Mapping for Turcicum Leaf Blight Resistance in Maize (Zea Mays L.) - Jakhar, Dan Singh; Singh, Rajesh; Singh, Shravan Kumar (Bangladesh Journal of Botany, 2022)
Turcicum leaf blight (TLB) is a prevalent maize disease found throughout the world, including India. To identify quantitative trait loci (QTLs) for TLB resistance with the help of appropriate mapping populations, namely F2:3 families and F2:6 families or recombinant inbred lines (RILs) evaluated in two environments were investigated. The cross CM 212 × V 336 was selected to generate the F2:3 families and the established F2:3 mapping population of cross CM 212 x CM 145 was further advanced to generate the F2:6 families for construction of linkage map and mapping of QTLs. The present investigation identified a total of 23 QTLs for TLB resistance in maize. Out of these QTLs, Nine QTLs were found in Linkage Group 4 (LG 4), followed by four QTLs in LG 2, two QTLs in each of LG 1, 3, 5 and 9 and one QTL in each of LG 6 and 7. On the other hand, the LOD values for these QTLs ranged from 2.64 to 14.84 in individual environments and over environments for both mapping populations, while the associated R2 values ranged from 10.80 to 18.98. The majority of the QTLs had over dominance at their respective chromosomes due to gene action. Bangladesh J. Bot. 51(2): 199-206, 2022 (June)